A systematic review and meta-analysis on the safety of newly adjuvanted vaccines among older adults. Issue 29 (5th July 2018) - Baay, Marc; Bollaerts, Kaatje; Verstraeten, Thomas
Highlights: First systematic review of safety of newly adjuvanted vaccines in older adults. No increased risk of Serious Adverse Events and deaths was shown. A slightly increased risk of Unsolicited Adverse Events was shown. A higher reactogenicity was observed for adjuvants AS01/AS02 and AS03. Risk of Solicited Adverse Events was not increased for MF59, except for pain. Abstract: Introduction: New adjuvants have been developed to improve the efficacy of vaccines and for dose-sparing capacity and may overcome immuno senescence in the elderly. We reviewed the safety of newly-adjuvanted vaccines in older adults. Methods: We searched Medline for clinical trials (CTs) including new adjuvant systems (AS01, AS02, AS03, or MF59), used in older adults, published between 01/1995 and 09/2017. Safety outcomes were: serious adverse events (SAEs); solicited local and general AEs (reactogenicity); unsolicited AEs; and potentially immune-mediated diseases (pIMDs). Standard random effects meta-analyses were conducted by type of safety event and adjuvant type, reporting Relative Risks (RR) with 95% confidence intervals (95% CI). Results: We identified 1040 publications, from which we selected 7, 7, and 12 CTs on AS01/AS02, AS03 and MF59, respectively. 47, 602 study participants received newly-adjuvanted vaccine and 44, 521 control vaccine, or placebo. Rates of SAEs (RR = 0.99, 95% CI = 0.96–1.02), deaths (RR = 0.99, 95% CI = 0.92–1.06) and pIMDs (RR = 0.94, 95% CI = 0.79–1.1) were comparable in newly-adjuvanted and control groups. Vaccine-related SAEs occurred in <1% of the subjects in both groups. The reactogenicity of AS01/AS02 and AS03 adjuvanted vaccines was higher compared to control vaccines, whereas MF59-adjuvanted vaccines resulted only in more pain. Grade 3 reactogenicity was reported infrequently, with fatigue (RR = 2.48, 95% CI = 1.69–3.64), headache (RR = 2.94, 95% CI = 1.24–6.95), and myalgia (RR = 2.68, 95% CI = 1.86–3.80) occurring more frequently in newly-adjuvanted groups. Unsolicited AEs occurred slightly more frequently in newly-adjuvanted groups (RR = 1.04, 95% CI = 1.00–1.08). Conclusions: Our review suggests that, within the clinical trial setting, the use of new adjuvants in older adults has not led to any safety concerns, with no increase in SAEs or fatalities. Higher rates for solicited AEs were observed, especially for AS01/AS02 and AS03 adjuvanted vaccines, but AEs were mostly mild and transient. Further evidence will need to come from the use of new adjuvants in the real-world setting, where larger numbers can be studied to potentially detect rare reactions.